1981
DOI: 10.1111/j.1365-2621.1981.tb04484.x
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Chemical Characteristics of Bovine Plasma Proteins Isolated as a Metaphosphate Complex

Abstract: A protein isolate was prepared from edible beef plasma by complexing the proteins with sodium hexametaphosphate. The isolate contained 82% protein which was completely soluble within the pH range 5.0-8.0. Foam volumes of solutions of the phosphated protein was greater than those observed in egg albumen or in plasma proteins prepared by the ultrafiltration process. Electrophoretic resolution revealed small differences in the protein species in phosphated plasma isolates and that prepared by ultrafiltration. Amm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

1986
1986
2009
2009

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 13 publications
0
7
0
Order By: Relevance
“…BLOOD COLLECTED from meat animals at slaughter has received considerable attention concerning its use as a food ingredient (Satterlee, 1981). Various collection and fractionation techniques have been used to produce both plasma-and red blood cell-based protein preparations (Tybor et al, 1973(Tybor et al, , 1975Donnelly and Delaney, 1977;Graham, 1978;Imeson et al, 1978;Danish Meat Research Institute 1980, 198 I;Etheridge et al, 1981). Plasma functionality has been studied in emulsions (Satterlee and Free, 1973;Tybor et al, 1973Tybor et al, , 1975Comer, 1979;Terre11 et al, 1979;Caldironi and Ockerman, 1982).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…BLOOD COLLECTED from meat animals at slaughter has received considerable attention concerning its use as a food ingredient (Satterlee, 1981). Various collection and fractionation techniques have been used to produce both plasma-and red blood cell-based protein preparations (Tybor et al, 1973(Tybor et al, , 1975Donnelly and Delaney, 1977;Graham, 1978;Imeson et al, 1978;Danish Meat Research Institute 1980, 198 I;Etheridge et al, 1981). Plasma functionality has been studied in emulsions (Satterlee and Free, 1973;Tybor et al, 1973Tybor et al, , 1975Comer, 1979;Terre11 et al, 1979;Caldironi and Ockerman, 1982).…”
Section: Introductionmentioning
confidence: 99%
“…Plasma functionality has been studied in emulsions (Satterlee and Free, 1973;Tybor et al, 1973Tybor et al, , 1975Comer, 1979;Terre11 et al, 1979;Caldironi and Ockerman, 1982). foams (Tybor et al, 1975;Etheridge et al, 1981) and gels (Harper et al, 1978;Comer, 1979;Hickson et al, 1980Hickson et al, , 1982. Plasma has also been used as a meat binding agent (Suter et al, 1976;Seideman et al, 1979;Siegel et al, 1979;Howell and Lawrie, 1984).…”
Section: Introductionmentioning
confidence: 99%
“…The six isolates were lyophilized. Another isolate was prepared according to Etheridge et al (1981): sodium hexametaphosphate solution (0.6N) added to plasma at a 5:l ratio and pH adjusted to 4.4 with 3N HCl. The precipitate was separated like other isolates and the pH adjusted to 7.0 with 0.125N NaOH and lyophilized.…”
Section: Methodsmentioning
confidence: 99%
“…1980 Protein recovery was over 90% for all isolates except isolate HCl-NaOH pH 4.4 which was 65%. Etheridge et al (1981) reported a higher protein recovery (93%) and a lower phosphorus content (1.8%) for plasma isolate. Isolate HCl-NaOH pH 4.4 was prepared under the same conditions specified by Etheridge et al (1981) except for the centrifugation process which was not specified in their study.…”
Section: Gelationmentioning
confidence: 96%
“…There are only a few studies available on the foaming properties of whole blood plasma , Etheridge et al 1981, Hill and Hall 1987. Foaming capacity of blood plasma proteins was reported to be equivalent to that of egg albumen (Tybor et al 1975, Hill andHall 1987) and superior to those of casein, whey proteins, and soy isolate proteins (Hill and Hall 1987).…”
Section: Blood Plasma Proteinsmentioning
confidence: 99%